Faktor Yang Berhubungan Dengan Pemanfaatan Antrean Online (Mobile JKN) Di RSUD Nene Mallomo Kabupaten Sidenreng Rappang - cindi agustina Usman; Sunandar Said; Devy Febrianti; Pratiwi Ramlan (Jurnal Kesehatan Marendeng, 2026)
The development of digital technology has driven increased efficiency in healthcare services through the Mobile JKN online queue, but its utilization has not been optimal. Based on the decline in utilization from 78.83% (August 2025) to 66.14% (September 2025). This study aims to analyze the related factors and analyze the most dominant factors with the utilization of the Mobile JKN online queue based on the Unified Theory of Acceptance and Use of Technology model. This type of research uses a quantitative method with a cross-sectional approach. The research instrument is a Guttman scale questionnaire that has passed validity and reliability tests. The study population is an average of 3,734 outpatient visits per month with a sample of 97 respondents selected using accidental sampling techniques. Data collection was carried out through observation, questionnaires, and documentation, then analyzed using the Chi-Square test (bivariate) and logistic regression test (multivariate). The results of the bivariate test show that performance expectations, effort expectations, social influence, and facilitating conditions have a significant relationship with the utilization of online queues with a p value <0.001. The results of the logistic regression test show that the facilitating conditions variable is the most dominant factor influencing the use of online queues with a Wald value of 9.954 and an OR value of 0.106 (95% CI: 0.026-0.427). Hospitals and BPJS Kesehatan are expected to prioritize strengthening facilitating conditions as the most dominant factor by providing stable internet access, improving application system reliability, and offering staff assistance for application use, so that the utilization of online queues can increase in a concrete and sustainable manner.